Experimental poisoning by Crotalaria lanceolata and Crotalaria pallida seeds in broilers Intoxicação experimental pelas sementes de Crotalaria lanceolata E. Mey. e Crotalaria pallida Aiton. em frangos de corte - Savaris T.* (2019)
© 2019 Colegio Brasileiro de Patologia Animal. All rights reserved.Crotalaria lanceolata E. Mey. and Crotalaria pallida Aiton. are leguminous plants of family Fabaceae found in most of the Brazilian territory. They were initially used as green manure and due their easy spread they are currently considered weeds in crops. Soybean and corn contamination can occur through the mechanical harvesting of these grains along with seeds of the Crotalaria species, which end up in the formulation of feed for production animals. Crotalaria spp. genus has toxic pyrrolizidine alkaloids (PA). Most plant species belonging to this genus can cause acute or chronic liver injury. In a first stage, one-day old broilers were divided into three groups: Group A (C. pallida seeds), Group B (C. lanceolata seeds), and Group C (Control). Groups A and B were divided into five subgroups, each with eight broilers, which received the following doses of the respective seeds in feed as of the 7th day of age: daily doses of 0.4%, 0.8% and 2.5%, and single doses of 15% and 25%. Four broilers in each study group were euthanized at 28 days of age - completing 21 days of seed consumption, and the four remaining broilers were euthanized at 42 days of age - completing 35 days of seed consumption. In a second stage, experiments were conducted using seeds of both the aforementioned plants with 28-day old broilers. These were divided into three groups of four animals each: Group D (C. pallida seeds) and Group E (C. lanceolata seeds), which received the respective seeds at daily doses of 1% and 2% in feed for 20 days, and Group F (Control). These broilers were euthanized when they were 80 days old. C. lanceolata seeds showed higher toxicity to broilers than C. pallida seeds, both supplied as of the 7th day of life. Clinical signs included inappetence, ruffled feathers, and brown diarrhea. The following gross lesions were observed: subcutaneous edema, ascites, hydropericardium, yellowish liver with hypertrophy or atrophy and enhanced lobular pattern, and distended gallbladder. Histologic lesions present in all birds in varying degrees were characterized by tumefaction and vacuolar degeneration of hepatocytes. The following clinical conditions and gross lesions were observed in the broilers: hepatocyte megalocytosis and karyomegaly, slight biliary epithelial hyperplasia, eosinophilic spheroids, and nuclear invagination with loss of hepatocyte cord architecture.